2021
DOI: 10.1371/journal.pone.0251089
|View full text |Cite
|
Sign up to set email alerts
|

Ambient urban N deposition drives increased biomass and total plant N in two native prairie grass species in the U.S. Southern Great Plains

Abstract: Remnants of native tallgrass prairie experience elevated atmospheric nitrogen (N) deposition in urban areas, with potential effects on species traits that are important for N cycling and species composition. We quantified bulk (primarily wet) inorganic N (NH4+-N + NO3--N) deposition at six sites along an urban development gradient (6–64% urban) in the Dallas-Fort Worth metropolitan area from April 2014 to October 2015. In addition, we conducted a phytometer experiment with two common native prairie bunchgrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, bulk Nr deposition has been shown to be comparable to wet Nr deposition (Cook et al., 2018; Decina et al., 2018), and it is often assumed to approximate wet Nr deposition where only bulk deposition is measured (Bettez & Groffman, 2013; Ponette‐González et al., 2021). Although we found general agreement between the IER and wet deposition results, our results suggest that there is seasonal variability in the amount of dry deposition captured by the IERs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, bulk Nr deposition has been shown to be comparable to wet Nr deposition (Cook et al., 2018; Decina et al., 2018), and it is often assumed to approximate wet Nr deposition where only bulk deposition is measured (Bettez & Groffman, 2013; Ponette‐González et al., 2021). Although we found general agreement between the IER and wet deposition results, our results suggest that there is seasonal variability in the amount of dry deposition captured by the IERs.…”
Section: Discussionmentioning
confidence: 99%